In vitro evaluation of the cytotoxicity of different self-adhesive resin cements - Necla Demir; Firdevs Kahvecioğlu; Muhammet Karcı; Hayriye Esra Ülker; Nuray Günaydın (Gazi University, 2018)
Objective: The aim of this in vitro study was to evaluate the cytotoxicity of three different self-adhesive resin cements. Materials and Method: Standardized test samples (2×5 mm) of adhesive resin cements ICEM (Heraeus Kulzer, Hanau, Germany), Nova Resin (Imicryl, Konya, Turkey) and Clearfil SA Cement (Kuraray, Okuyama, Japan) were prepared according to the manufacturers' instructions. Bovine dental pulp-derived cells (Clonal SV40) were seeded into the wells of a 96 well-plate, and incubated in MEM Alpha (Gibco Invitrogen) supplemented with 20% fetal bovine serum, 5% penicillin/streptomycin, 1% geneticin in a humidified atmosphere of 5% CO2. The test samples were immersed in the growth medium for 24 h and the extracts were applied onto the cells. A group of cells was immersed in the growth medium that was not exposed to the test materials, and was assigned as negative control. The cell viability was determined by enzyme activity tests at the end of a 24 h treatment period. The data were statistically analyzed using one-way ANOVA. Results: There was no statistically significant difference between the cell viability of the negative control group and ICEM, Clearfil SA and Nova Resin Cement groups (p>0.05). There was also no statistically significant difference among the self-adhesive resin cement groups (p>0.05). Conclusion: In this in vitro study, self-adhesive resin cements were found to have no significant cytotoxic effects on two dimensional dental bovine pulp cells.